LINC01137/miR-186-5p/WWOX: a novel axis identified from WWOX-related RNA interactome in bladder cancer - Kołat, Damian; Kałuzińska-Kołat, Żaneta; Kośla, Katarzyna; Orzechowska, Magdalena; Płuciennik, Elżbieta; Bednarek, Andrzej K. (Frontiers in Genetics, 2023)
Introduction: The discovery of non-coding RNA (ncRNA) dates back to the pre-genomics era, but the progress in this field is still dynamic and leverages current post-genomics solutions. WWOX is a global gene expression modulator that was scarcely investigated for its role in regulating cancer-related ncRNAs. In bladder cancer (BLCA), the link between WWOX and ncRNA remains unexplored. Description of the AP-2α and AP-2γ transcription factors, known as WWOX-interacting proteins, is more commonplace regarding ncRNA but still merits investigation. Therefore, this in vitro and in silico study aimed to construct an ncRNA-containing network with WWOX/AP-2 and then investigate the most relevant observation in the context of BLCA cell lines and patients. Methods: RT-112, HT-1376, and CAL-29 cell lines were subjected to two stable lentiviral transductions. High-throughput sequencing of cellular variants (deposited in the GEO database under GSE193659 record) enabled the WWOX/AP-2–dependent differences to be investigated using various bioinformatics tools (e.g., limma-voom, FactoMineR, mSVM-RFE, miRDB, Arena-Idb, ncFANs, RNAhybrid, TargetScan, PANTHER, GTRD, or EvaluateCutpoints) and repositories such as TCGA and CCLE. The most relevant observations from CAGE-Seq were certified using Real-time PCR, whereas TCGA data were validated using the GSE31684 cohort. Results: The first stage of the whole study justified focusing solely on WWOX rather than on WWOX combined with AP-2α/γ. The most relevant observation of the developed ncRNA-containing network was LINC01137, i.e., lncRNA that unraveled the core network containing UPF1, ZC3H12A, LINC01137, WWOX, and miR-186-5p, the last three being a novel lncRNA/miRNA/mRNA axis. Patients’ data confirmed the LINC01137/miR-186-5p/WWOX relationship and provided a set of dependent genes (i.e., KRT18, HES1, VCP, FTH1, IFITM3, RAB34, and CLU). Together with the core network, the geneset was subjected to survival analysis of both TCGA-BLCA and GSE31684 patients, which indicated that, e.g., increased expression of WWOX or LINC01137 is favorable, similar to their combination with each other (WWOX↑ and LINC01137↑) or with MIR186 (WWOX↑/LINC01137↑ but MIR186↓). Conclusion: WWOX is implicated in the positive feedback loop with LINC01137 that sponges WWOX-targeting miR-186-5p. This novel WWOX-containing lncRNA/miRNA/mRNA axis should be further investigated to depict the relationships in a broader context, which could contribute to BLCA research and treatment.